(untitled) (Research, Society and Development, 2022)
Introduction: Epidemiological studies demonstrate a high prevalence of signs and/or symptoms of Temporomandibular Disorder (TMD) in the adult population. However, few studies have evaluated this dysfunction in primary healthcare. Aim: To assess the prevalence of TMD symptoms, associated factors and impact on quality of life in users of the primary healthcare network in the city of Maceió/AL. Method: 108 participants were evaluated for the presence of TMD symptoms (anamnestic index DMF), symptoms suggestive of anxiety and depression (Hospital Anxiety and Depression scale - HAD) and symptoms suggestive of stress (Adult Stress Symptoms Inventory - ISSL); in addition to quality of life related to oral health, assessed by the abridged version of the Oral Health-related (OHIP-14). Results: 55.6% had symptoms of TMD and 19.4% showed a need for treatment. Female gender and self-report of parafunctional habits were predictors for TMD symptoms, and stress and habits, for treatment need. TMD symptoms, even mild, had a negative impact on quality of life. Conclusion: Thus, the results presented suggest the need for preparation and organization of the healthcare network, at different levels, to ensure adequate access and treatment for patients with TMD and Orofacial Pain.